Edwardsiella piscicida YefM-YoeB: A Type II Toxin-Antitoxin System That Is Related to Antibiotic Resistance, Biofilm Formation, Serum Survival, and Host Infection - Ma, Dongmei; Gu, Hanjie; Shi, Yanjie; Huang, Huiqin; Sun, Dongmei; Hu, Yonghua (Frontiers in Microbiology, 2021)
The emergence of drug resistant bacteria is a tricky and confronted problem in modern medicine, and one of important reasons is the widespread of toxin-antitoxin (TA) systems in pathogenic bacteria. Edwardsiella piscicida (also known as E. tarda) is the leading pathogen threatening worldwide fresh and seawater aquaculture industries and has been considered as a model organism for studying intracellular and systemic infections. However, the role of type II TA systems are completely unknown in aquatic pathogenic bacteria. In this study, we identified and characterized a type II TA system, YefM-YoeB, of E. piscicida, where YefM is the antitoxin and YoeB is the toxin. yefM and yoeB are co-expressed in a bicistronic operon. When expressed in E. coli, YoeB cause bacterial growth arrest, which was restored by the addition of YefM. To investigate the biological role of the TA system, two markerless yoeB and yefM-yoeB in-frame mutant strains, TX01ΔyoeB and TX01ΔyefM-yoeB, were constructed, respectively. Compared to the wild strain TX01, TX01ΔyefM-yoeB exhibited markedly reduced resistance against oxidative stress and antibiotic, and markedly reduced ability to form persistent bacteria. The deletion of yefM-yoeB enhanced the bacterial ability of high temperature tolerance, biofilm formation, and host serum resistance, which is the first study about the relationship between type II TA system and serum resistance. In vitro infection experiment showed that the inactivation of yefM-yoeB greatly enhanced bacterial capability of adhesion in host cells. Consistently, in vivo experiment suggested that the yefM-yoeB mutation had an obvious positive effect on bacteria dissemination of fish tissues and general virulence. Introduction of a trans-expressed yefM-yoeB restored the virulence of TX01ΔyefM-yoeB. These findings suggest that YefM-YoeB is involved in responding adverse circumstance and pathogenicity of E. piscicida. In addition, we found that YefM-YoeB negatively autoregulated the expression of yefM-yoeB and YefM could directly bind with own promoter. This study provides first insights into the biological activity of type II TA system YefM-YoeB in aquatic pathogenic bacteria and contributes to understand the pathogenesis of E. piscicida.